Capacity Building untuk Pengembangan Program Studi Kependidikan Islam: Capacity Building for the Development of Islamic Education Study Programs - Moch. Imam Machfudi (Fenomena, 2011)
Capacity building is an ongoing process to improve the ability of individuals, groups, organizations, and academics to identify and address challenges in institutional development. In institutions such as the Islamic Education Study Program – the State College of Islamic Studies (STAIN) Jember, capacity building should be viewed as an effort to develop human resources (HR) in three areas: (1) organizational development, (2) partnership, and (3) civil society strengthening. This aims to achieve the independence of the study program. Capacity building adalah proses berkelanjutan untuk meningkatkan kemampuan individu, kelompok, organisasi, dan akademisi dalam mengidentifikasi dan menghadapi tantangan pengembangan suatu lembaga. Capacity building dalam lembaga seperti Program Studi Kependidikan Islam – Sekolah Tinggi Agama Islam Negeri (STAIN) Jember perlu dipandang sebagai upaya pengembangan sumber daya manusia (SDM) dalam tiga aspek, yaitu: (1) pengembangan organisasi, (2) kemitraan, dan (3) penguatan masyarakat sipil. Tujuan ini dimaksudkan untuk mencapai kemandirian program studi.